Differential Diagnosis of Entamoeba spp. Using the 18SrRNA Gene in Gastroenteritis Patients - Farhan, Sabaa Muhsen; Abdulrazzaq, Sumaya Ayad; Mohammed, Akram Jassam (Iraqi Journal of Science, 2024)
In order to accurately diagnose Entamoeba spp., this study’s major goal was to develop a proof-of-concept method for simultaneously detecting pathogenic and non-pathogenic amoebae using DNA. During amoebiasis, two diagnostic techniques (microscopic inspection and PCR techniques with particular primers) were evaluated. About 100 feces samples from Fallujah individuals who had clinical symptoms were taken. The outcome reveals that only 20 samples have Entamoeba spp. infections. According to this study, the two species had distinct infection percentages. Entamoeba histolytica was the most prevalent infection, at 85%, followed by Entamoeba dispar, which was 15% of all the Entamoeba-positive samples. In addition to studying the morphology and genes of the positive samples, the residential environment, age, and gender were also taken into consideration. It showed the infective patients in the rural area had a higher rate of infection, which was 18%, while the infection in the urban area was less, which was represented by 2%. As for the effect of the age factor, the highest percentage was from children who did not exceed ten years old, which was 10%. The lowest percentage was 2% for people over the age of sixteen (16). According to the gender factor, a different percentage appeared in males than females. The result showed a high infection rate for males, which was estimated at about 16%, but for females it was much less, at only 4%.